Bioativos naturais como fator de proteção ultravioleta para tecidos de algodão: uma alternativa promissora e sustentável de proteção natural - Santos, Arielma Marques dos (2023)
Solar radiation, although essential for the maintenance of life, is associated with a multitude of impacts on human health, such as premature skin aging and most skin cancers, affecting millions of people worldwide annually. To prevent the manifestation of these diseases, the use of various methods available on the market is widely recommended, with clothing being an attractive and advantageous choice. In this work, natural bioactives were used as ultraviolet protection factor in cotton fabrics, in order to add more value and potential to the cultivation of plants from the northeast region (Green Coconut, Bixa orellana, and Curcuma longa L.) for photoprotective purposes in the production of everyday cotton-based clothing. Extracts from the mesocarp of green coconut (10.0%, 5.0%, and 2.5% w/v), seeds of Bixa orellana (37.5%, 25.0%, and 12.5% w/v), and powders of Curcuma longa L. (37.5%, 25.0%, and 12.5% w/v) were applied to raw cotton fabrics (Tc). The dye impregnation was performed by immersing the fabric samples in the suspensions of bioactive extracts. The results of Fourier-transform infrared spectroscopy (FTIR) of the fibers from the mesocarp of green coconut and the powders of Bixa orellana and Curcuma longa L. showed the presence of tannins, bixin and norbixin, and curcumin, respectively, dyes associated with anti-UV properties. UV/Vis molecular absorption spectroscopy was essential for characterizing the performance of fabrics when impregnated with dyes from bioactive extracts. It was able to improve the photoprotection properties of the cotton fabric, as evidenced by increased absorbance and reflectance (%) and decreased transmittance (%) in the ultraviolet region, as well as higher UPF values. The extracts used in the samples Tc+EXBO37.5%, Tc+EXCLind37.5%, Tc+EXCLind23.0%, Tc+EXCLind10.0%, and Tc+EXCLriz10.0% were able to provide adequate protection against ultraviolet radiation to the cotton fabrics, with the bioactive extracted from Curcuma longa L. showing the best photoprotection performance. Although the other concentrations of bioactives did not provide adequate photoprotection to the fabric, they all increased the UPF values, demonstrating their potential for investigation in this application. Finally, it is worth noting that this work has used a simple, practical, and low-cost methodology, which, in addition to contributing to protection against damage caused by ultraviolet radiation in everyday clothing production, can add socioeconomic value and socio-environmental development to the northeast region, producer of the species Cocos nucifera, Bixa orellana, Curcuma longa L., and cotton fabrics.